2017
DOI: 10.1177/1687814017695959
|View full text |Cite
|
Sign up to set email alerts
|

Energy-efficient job shop scheduling problem with variable spindle speed using a novel multi-objective algorithm

Abstract: Most traditional scheduling problems prioritize optimizing production efficiency, cost, and quality. However, with gradually increasing energy consumption and environmental pollution, the novel ''energy-efficient scheduling'' model has received increasing attention from scholars and engineers. This scheduling model focuses on reducing workshop energy consumption and environmental pollution and has become a hot topic in the scheduling area. This article proposes a new energy-efficient scheduling mathematical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Li et al [13] presented a suggested multiobjective optimization algorithm using crossover agents to minimize energy consumption. Considering the speed level and machine turn on/off, the researchers [14][15][16][17] proposed a genetic algorithm to minimize makespan and energy consumption. e basis of the analysis of the algorithms is based on the investigation in physical space.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al [13] presented a suggested multiobjective optimization algorithm using crossover agents to minimize energy consumption. Considering the speed level and machine turn on/off, the researchers [14][15][16][17] proposed a genetic algorithm to minimize makespan and energy consumption. e basis of the analysis of the algorithms is based on the investigation in physical space.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the rule, position values in 1 X are first ranked in an increasing order, then the operation permutation can be acquired according to the new order, which is shown in Figure 4. For the speed-level selection segment, the conversion process can be modified from the method proposed by Yuan and Xu [40], which can be represented by Equation (19). z(j) denotes the size of alternative speed-level set for the operation corresponding to the jth element, u(j) means the selected speed level, u(j) ∈ [1, z(j)].…”
Section: Conversion From Individual Position Vector To Scheduling Solmentioning
confidence: 99%
“…The conversion process is shown in Figure 7. For the speed-level selection segment, the conversion is generally an inverse process of Equation (19). However, there is a special case, that is, z(j) = 1, x(j) is obtained by choosing a random value between [−ε, ε].…”
Section: Conversion From Scheduling Solution To Individual Position Vmentioning
confidence: 99%
See 1 more Smart Citation
“…It presents a synchronous switch control method to schedule the system such that it can achieve the performance of one with two inverts. The 11th article, authored by Yin et al, 19 reports a method for job shop scheduling for energy efficiency, productivity increase, and noise reduction by controlling the machine spindle speed. The problem is formulated as a mixed integer programming problem and a genetic algorithm is developed to solve the problem.…”
mentioning
confidence: 99%